2017
DOI: 10.1186/s12905-017-0467-y
|View full text |Cite
|
Sign up to set email alerts
|

“Is it menopause or bipolar?”: a qualitative study of the experience of menopause for women with bipolar disorder

Abstract: BackgroundMenopause can be a time of change for women and may be marked by disturbances in mood. For women living with a mental illness, such as bipolar disorder, little is known about how they experience mood changes during menopause. This study aimed to explore how women with bipolar disorder constructed mood changes during menopause and how this impacted on treatment decisions.MethodsSemi-structured interviews were undertaken with fifteen women who reported they had been diagnosed with bipolar disorder. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…There was no significant association between hot flash severity and sleep disturbance and mania symptom scores. This result partially supports findings of prior qualitative research where some women reported that they experienced sleep disturbances as a result of hot flash symptoms and that this in turn had an impact on mood symptoms 21 . As only depression seemed to be associated with sleep and hot flash severity in the present study, further research is needed to examine whether menopause symptoms may have an impact on mania symptoms for women living with bipolar disorder.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was no significant association between hot flash severity and sleep disturbance and mania symptom scores. This result partially supports findings of prior qualitative research where some women reported that they experienced sleep disturbances as a result of hot flash symptoms and that this in turn had an impact on mood symptoms 21 . As only depression seemed to be associated with sleep and hot flash severity in the present study, further research is needed to examine whether menopause symptoms may have an impact on mania symptoms for women living with bipolar disorder.…”
Section: Discussionsupporting
confidence: 89%
“…There is limited research examining the experience of hot flashes for women with a bipolar disorder, in particular the relationship between hot flashes and bipolar symptoms 6 . A recent qualitative study found that women with bipolar disorder who experienced hot flashes also reported sleep disturbances, which had an impact on mood symptoms 21 . Addressing sleep disturbances has been described as an important aspect of the management of bipolar disorder, as sleep changes are both a key symptom 2 and potential cause of mood episodes for people living with this condition 22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies focused on the menopausal experience of women with diseases. For example, some studies have investigated how autistic women deal with major life changes during the menopausal transition in middle age [ 26 ] and their understanding of the positive and negative aspects of menopausal changes [ 27 ]; other studies focus on how bipolar affective disorder patients experience mood changes during menopause and the impact on their treatment decisions [ 28 ]. In addition, some scholars have called for research on migrant and refugee women related to sexual embodiment, including menopause, to promote sexual and reproductive health and understand gender subjectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 15% of more than 20 million women experiencing menopause each year in the United States are also diagnosed with a mood disorder, including bipolar disorder (BD) and major depressive disorder (MDD). 1 Quantitative 2 , 3 and limited qualitative research 4 , 5 indicate women diagnosed with a mood disorder might experience an increase in depressive, hypomanic, or manic symptoms during perimenopause and postmenopause.…”
Section: Introductionmentioning
confidence: 99%